A Comparison of the Antioxidant Potential and Metabolite Analysis of Marine Fungi Associated with the Red Algae Pterocladiella capillacea from Northern Taiwan - Jiji Kannan; Ka-Lai Pang; Ying-Ning Ho; Pang-Hung Hsu; Li-Li Chen (MDPI AG, 2024)
This study represents a primary investigation centered on screening six marine fungi, Emericellopsis maritima, Engyodontium album, Hypomontagnella monticulosa, Hortaea werneckii, Trichoderma harzianum, and Aspergillus sp.7, associated with the red algae Pterocladiella capillacea, which was collected from Chao-Jin Park in Keelung, Taiwan, as potential immunostimulants for shrimp aquaculture. Recognizing the imperative for novel strategies to combat pathogen resistance arising from the use of antibiotics and vaccines in aquaculture, this study aimed to evaluate the metabolomic profile, antioxidant capabilities, and antibacterial properties of marine fungi. The antibacterial activity of the fungal extract was evaluated against five major aquaculture pathogens: Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Enterobacter aeruginosa, and Vibrio parahaemolyticus. The viability and cytotoxicity of marine fungal extracts were preliminarily evaluated using brine shrimps before assessing cytotoxicity, growth performance, immune efficacy, and disease resistance in white shrimp. The present study demonstrated that total phytochemical analysis correlated with antioxidant activity. Emericellopsis maritima and Trichoderma harzianum exhibited the strongest DPPH antioxidant scavenging activities of half-maximal inhibitory concentration (IC50) 16.5 ± 1.2 and 12.2 ± 2.6, which are comparable to ascorbic acid. LC-HDMSE analysis of the marine fungal extracts identified more than 8000 metabolites mainly classified under the superclass level of organic oxygen compounds, Organoheterocyclic compounds, Phenylpropanoids and polyketides, alkaloid and derivatives, benzenoids, lignans and neolignans, lipid and lipid-like molecules, nucleotides and nucleosides, organic nitrogen compounds, and organic acids and derivatives. Overall, our study significantly contributes to the advancement of sustainable practices by exploring alternative antimicrobial solutions and harnessing the bioactive potential inherent in marine endophytic fungi. In conclusion, our study advances our comprehension of fungal communities and their applications and holds promise for the development of effective and environmentally friendly approaches for enhancing shrimp health and productivity.